Norm Referenced Test Sebagai Metode Penilaian Berdasarkan Kelompok Kelas - Herman Darmawan; Nuril Huda; Dina Hermina (Lembag, 2024)
There are two ways to process test results to determine graduation standards, namely Norm Referenced Test (NRT) and Criteria Referenced Test (CRT). However, they differ in data processing function, which affects the outcome of data processing. Because the author tends to process score results based on norms with the reasoning that there are no absolute provisions put forth by one party in one direction. Therefore, through this article, the author tries to explain in depth about this Norm Referenced Test along with examples of score processing. This study uses a literature review with a qualitative approach. The results of this study show that with Norm Referenced Test, students' graduation will be determined by summing up or finding the average score from the final learning outcomes, and that's how they will be declared as either passing or failing participants. Like the test results processing discussion, where out of 25 students, after calculating the average score it was found to be 67.92, therefore if a student's score does not meet this requirement, they will be declared as not passing. This means among the group table receiving scores below 65 will need remedial, while scores of 70 and above are declared passing..